Diabetes Mellitus Type 2 Medication Rationality Evaluation of Kampung Bali Clinic Outpatient from January to December 2015 - ., Ef Yudi Harjo (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2015)
Diabetes mellitus (DM) is a metabolism disorder associated with abnormal carbohydrate metabolism, fat, and proteins caused by decreased insulin secretion which leads to hyperglycemia. The purpose of this study is to determine and evaluates the rationality of DM type 2 in outpatient Clinics in Kampung Bali, Pontianak from January to December 2015. This study is a nonexperimental research which utilizes descriptive cross-sectional design. Data were collected retrospectively from medical record of patients who suffers from DM 2. Data obtained were analyze with PERKENI 2011 Standards. The results show that the antidiabetic drugs used for DM type 2 patients in Clinics of Kampung Bali in Pontianak were 62,96% of metformin, 22,22% of glibenclamide, and the combination of both of these types of drugs up to 14,81%. The rationality of type 2 DM patient treatment in Clinics of Kampung Bali City Pontianak, compared to the PERKENI 2011 standards for 27 cases in Kampung Bali Clinic in Pontianak, indication suitability was 96.30%, and suitability of dosing, medication and patients were 100%.